1995
DOI: 10.1002/art.1780380521
|View full text |Cite
|
Sign up to set email alerts
|

A fatal pulmonary complication of lupus in pregnancy

Abstract: Pulmonary vasculitis is an uncommon complication of systemic lupus erythematosus (SLE), and has not been previously documented in pregnancy. This case report describes the rapidly fatal course of a pregnant SLE patient, whose terminal illness was manifested by severe pulmonary hypertension and unexpected autopsy findings of medium and large vessel vasculitis. The relationship of these unusual manifestations to other clinical and serologic features of SLE, as well as novel therapeutic options, are discussed.Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…PAH has been reported as a common cause of death in Chinese and Korean patients, but not a common cause of death in North American or European cohorts [3], suggesting that ethnicity or access to care may be prognostic factors for survival. Our recent systematic review of the literature [90] identified a number of clinical factors that may be associated with survival; magnitude of the elevation in P pa at diagnosis [78,89,91], thrombosis [89,92,93], thrombocytopenia [94], presence of an anti-cardiolipin antibody [89,92,93], concurrent pregnancy [95,96], infection [77], Raynaud's phenomenon [93,97], plexiform lesion [95] and pulmonary vasculitis [96]. Conversely, lupus central nervous system disease [89], lupus nephritis [89] and lupus disease activity [89,[98][99][100] have not been associated with survival in SLE-PH.…”
Section: Sle-associated Phmentioning
confidence: 99%
“…PAH has been reported as a common cause of death in Chinese and Korean patients, but not a common cause of death in North American or European cohorts [3], suggesting that ethnicity or access to care may be prognostic factors for survival. Our recent systematic review of the literature [90] identified a number of clinical factors that may be associated with survival; magnitude of the elevation in P pa at diagnosis [78,89,91], thrombosis [89,92,93], thrombocytopenia [94], presence of an anti-cardiolipin antibody [89,92,93], concurrent pregnancy [95,96], infection [77], Raynaud's phenomenon [93,97], plexiform lesion [95] and pulmonary vasculitis [96]. Conversely, lupus central nervous system disease [89], lupus nephritis [89] and lupus disease activity [89,[98][99][100] have not been associated with survival in SLE-PH.…”
Section: Sle-associated Phmentioning
confidence: 99%
“…25,[30][31][32] Findings include acute fibrinoid necrosis and vasculitis, as well as chronic intimal fibrosis, medial hypertrophy, alteration of elastic laminae, periadventitial fibrosis, aneurysmal dilation, and plexiform lesions, which are virtually identical to the alterations seen in patients with IPAH. 9,17,29 These changes occurred in arteries, arterioles, and veins. Occasional cases with thrombotic arteriopathy have also been reported and were found to correlate with a hypercoagulable status, including positive lupus anticoagulant and anticardiolipin antibodies.…”
Section: Pathologymentioning
confidence: 99%
“…38,39 In addition, when antiphospholipid antibodies bind to the phospholipids on the endothelial surface, there is resultant in-situ thrombosis and the release of soluble mediators and subsequent vascular injury. 9,37 Antiendothelial cell antibodies may also play a key pathogenic role in the development of SLE-PH. Systemic lupus erythematosus is an autoimmune disease characterized by polyclonal B cell activation.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors are incriminated for the induction of SLE-PH, such as hypoxic vasoconstriction, pulmonary venous hypertension resulting from left heart disease, antiphospholipid antibody-induced chronic or acute thrombosis, and pulmonary venoocclusive disease (PVOD) [83–88]. There are several pathological similarities in SLE-PH and IPAH, including SMCs hypertrophy, hyperactivation of transcription factors like hypoxia inducible factor-1 alpha and nuclear factor of activated T-lymphocytes, decreased expression of certain voltage-gated potassium channels, and de novo expression of antiapoptotic proteins [89].…”
Section: Pulmonary Arterial Hypertension Associated With Connectivmentioning
confidence: 99%